STEM IN ACTION: REAL-WORLD APPLICATIONS OF SCIENCE, TECHNOLOGY, ENGINEERING, AND MATH - Siregar, Nur Choiro; Warsito, Warsito; Gumilar, Aris; Amarullah, Ahmad; Rosli, Roslinda (Prima: Jurnal Pendidikan Matematika, 2024)
Science, Technology, Engineering, and Mathematics (STEM) is an interdisciplinary educational approach that focuses on the practical application of knowledge and skills in these four areas. STEM education aims to develop critical thinking, problem-solving, and analytical skills essential for success in the 21st century. STEM education has become increasingly important in recent years as technology has transformed nearly every aspect of our lives. This research aims to: (1) What are the benefits of STEM in-action projects? (2) how can STEM in-action projects be effectively implemented in educational and professional settings? (3) what are the real-world applications of STEM, and how are they impacting society? and (4) what is the future of STEM in action, and what trends and developments are shaping its direction? This research is a literature review involving 17 journals published in 2019-2023. The results of this study found that: (1) STEM can help the student to develop critical thinking skills, problem-solving skills, and creativity; (2) provide students with opportunities to work on authentic problems, promoting collaboration and teamwork, and provide professional development for educators; (3) healthcare, energy, and the environment, (4) data science and artificial intelligence; (4) the growing demand for STEM professionals, and the need for greater diversity and inclusivity in STEM fields. STEM in-action: Real-world applications of STEM is a concept that seeks to bridge the gap between theory and practice in STEM education. It is an approach that emphasizes applying STEM principles in real-world scenarios, allowing students to see how the concepts they learn in class are relevant to the world around them. STEM in action is a fundamental approach to STEM education that helps students develop practical skills and knowledge while preparing them for the challenges of the 21st century